2008
DOI: 10.1097/aog.0b013e3181637a82
|View full text |Cite
|
Sign up to set email alerts
|

Hospital, Simulation Center, and Teamwork Training for Eclampsia Management

Abstract: ISRCTN, http://isrctn.org, ISRCTN67906788, reference number 0270030.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 12 publications
1
149
1
2
Order By: Relevance
“…The SaFE study demonstrated that training maternity staff in the management of obstetric emergencies improved team and individual performance, individual knowledge, and patientactor perception of safety. 5,[31][32][33] Communication with patient-actors is an integral part of the local SaFE-studybased training course. Since the introduction of this compulsory training, attendance for all maternity staff (medical and non-medical, junior and senior) has ranged from 95 to Mackey score Figure 1.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The SaFE study demonstrated that training maternity staff in the management of obstetric emergencies improved team and individual performance, individual knowledge, and patientactor perception of safety. 5,[31][32][33] Communication with patient-actors is an integral part of the local SaFE-studybased training course. Since the introduction of this compulsory training, attendance for all maternity staff (medical and non-medical, junior and senior) has ranged from 95 to Mackey score Figure 1.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…It provides the opportunity to perform clinical decision-making without generating any risk to patients (Bond & Spillane, 2002). In addition, because a standardized curriculum can be provided and all students have the same experience (Ellis et al, 2008), it is considered to be an educational alternative that can overcome the limitations of the maternity nursing practicum.…”
Section: Effects Of Simulation-based Education On Communication Skillmentioning
confidence: 99%
“…6 Use for developing teamwork and leadership Emergencies often require the rapid mobilisation of an ad hoc multiprofessional team in order to avoid or limit harm. 4 This applies particularly to maternity care, but also to gynaecology. Many of the emergencies are rare and difficult to predict; the first time a maternity specialist encounters eclampsia might be as the most senior doctor available.…”
Section: Use After Certificationmentioning
confidence: 99%
“…9 The development of teamworking might require nothing more than local teams practising together; a study of eclampsia rehearsals found no additional benefit of specific training in teamwork. 4 …”
Section: Use After Certificationmentioning
confidence: 99%
See 1 more Smart Citation